Criticism of the reliability of archaeological dating of cultural artifacts - A. Soshnikov (Ukrainian Cultural Studies, 2020)
The purpose of the article is to join the discussion about the degree of reliability of archaeological dating of cultural artifacts. Research methodology of the article: the main methods of archaeological dating of cultural artifacts are analyzed. The following conclusions are presented in the article: the concept of "archaeological source" is one of the basic categories of archeology, which largely determines the empirical activity of a scientist. In the domestic science, the term still does not have a unified understanding, as, indeed, most categories theoretical level. Perhaps the only one an indisputable point in the definition of the term is what archaeological sources are both material remains and observations of the researcher during field and chamber work. In the course of the study, it was concluded that archeology is not capable of either confirming or refuting the traditional chronological scheme, since it is impossible to date objects of material culture without relying on written records. The only thing that archaeological methods can give so far is the establishment of the relative sequence of layers and cultures. But between these results and the absolute age of these layers, there is a gap that has been filled so far based on the traditional grid. Generalization of the main methods of archaeological dating of cultural artifacts represents the novelty of the article. The practical significance of the article is the correction of the existing methods of archaeological dating of cultural artifacts. Archeology is neither able to confirm nor refute the traditional chronological scheme, because the objects of material culture cannot be dated without relying on written records. When, it would seem, it is possible to date an architectural structure absolutely reliably, the obtained result contradicts traditional ideas. The only thing that archaeological methods can give so far is to establish the relative sequence of layers and cultures. But between these results and the absolute age of these layers – a whole gap, which is still filled, based on the traditional grid.